(3GdTPQGJ GdPgHjI aj JQGLe GdCFeI GdCKfi YTQjIs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjbg SejJg hbO CTGQ Edjge ai Vef bUjOg GdEeGe CHhGdaVd jMji Hf SdGeg GdMUcai s
(3BNQgG (B:s
(3SHMGf QHc QH GdYRg YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B190 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCMeOjg HLGeY GdRjJhfg HJhfS (B(5031) s
Keywords: (3GdJGQjNs